The role of haem in the mechanism of action of antimalarials in Plasmodium falciparum - Combrinck, Jill Michelle (Division of Clinical Pharmacology, 2017)
The malaria parasite detoxifies host red blood cell derived haem by conversion into the inert biocrystal haemozoin. Inhibiting this critical pathway is proposed to be the mechanism of action of chloroquine and related antimalarials and several studies have linked inhibition of the formation of synthetic haemozoin, β-haematin, to parasite survival. However, haemozoin inhibition with a dose related increase in "free" haem correlated to decreased survival has not been demonstrated in the parasite. This project investigated the role of haem in the mechanism of action of several clinically relevant and novel antimalarials in the malaria parasite, Plasmodium falciparum.